Basis Pengetahuan Web Semantik pada Pemodelan Sistem Pendukung Rekomendasi Jurusan Kuliah - Iwan Santosa; Panji Yudasetya Wiwaha; Bernard Renaldy Suteja (Maranatha University Press, 2023)
Prospective students have wider choice of opportunities as opposed to many choices of study majors offered by higher education institution. On the other hand, it can also cause difficulties for students to make the right choice. How a student make decision regarding his or her choice of study major is influenced by several factors, including student interest, majors chosen at the previous school level, students’ aspirations, as well as entry requirements at a particular university. This research aims to design a model of an information system that can make it easier for a student to obtain information about the most appropriate study program, among the many study programs offered by the university. The information generated by this system can be used as a reference to support recommendations for prospective students in deciding which study program they will choose appropriately. The system is designed by utilizing semantic web technology, by building an ontology based on several knowledge-bases to represent new knowledge. The ontology model designed in OWL format succeeded in connecting several knowledge-bases into comprehensive and contextual knowledge as a source of information that can be used by a prospective student to choose a study program based on these recommendations. Protege is used for ontology modeling, while implementation on the web server is done using Apache Jena platform.